Flow of cerebrospinal fluid is driven by arterial pulsations and is reduced in hypertension - Humberto Mestre (Nature Portfolio, 2018)
Arterial pulsations are thought to drive CSF flow through perivascular spaces (PVSs), but this has never been quantitatively shown. Using particle tracking to quantify CSF flow velocities in PVSs of live mice, the authors show that flow speeds match the instantaneous speeds of the pulsing artery walls that form the inner boundaries of the PVSs.